Increasing Tax Awerenes for Micro-Enterprise Entrepreneurs in Coastal Areas : An Education and Mentorship Approach - Sirajuddin; Natsaha Mazna Ramli; Muhammad Khaedar Sahib; Masdar Ryketeng; Muhammad Idrus; Achdian Anggreny Bangsawan; Miftha Farild (www.amertainstitute.com, 2025)
Micro-enterprises play a crucial role in supporting local economic growth, particularly in coastal areas where communities depend heavily on informal business activities such as fisheries, seafood processing, small trading, and water-based services. Despite their economic contribution, tax awareness among micro-enterprise entrepreneurs in these regions remains remarkably low, limiting their access to formal financial services and government support programs. This community engagement program aims to enhance tax awareness and compliance through an integrated education and mentorship approach specifically designed for coastal micro-business actors in South Sulawesi. The program incorporates interactive tax literacy training, hands-on mentoring, and practical demonstrations on administrative processes such as Taxpayer Identification Number (NPWP) registration, tax reporting, and the use of digital tax platforms. Collaboration with Universiti Sains Islam Malaysia, the International Association of Economic and Business, several local universities, community organizations, traditional institutions, and Masjid Terapung Ar-Rahma Tallo ensures a culturally grounded and community-based implementation strategy. The program addresses key issues faced by micro-entrepreneurs, including limited financial literacy, negative perceptions of taxation, minimal access to digital services, and the absence of personalized guidance. Findings indicate that the combination of contextual education and continuous mentorship significantly improves participants’ understanding, confidence, and willingness to comply with tax obligations. Beyond increasing tax awareness, the initiative strengthens community networks, enhances entrepreneurial capacity, and supports the development of a more inclusive and sustainable local economic ecosystem. This model offers a scalable framework for tax empowerment in underserved coastal communities.